2022
DOI: 10.1264/jsme2.me22012
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Potential of the Superphylum <i>Patescibacteria</i> Reconstructed from Activated Sludge Samples from a Municipal Wastewater Treatment Plant

Abstract: Patescibacteria are widely distributed in various environments and often detected in activated sludge. However, limited information is currently available on their phylogeny, morphology, and ecophysiological role in activated sludge or interactions with other microorganisms. In the present study, we identified microorganisms that interacted with Patescibacteria in activated sludge via a correlation analysis using the 16S rRNA gene, and predicted the metabolic potential of Patescibacteria using a metagenomic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…Patescibacteria are known for their small cell (e.g., average diameter of ~0.2 μm) (He et al, 2021) and genome (e.g., 1.1±0.2 Mbp) sizes (Tian et al, 2020;Kagemasa et al, 2022), and genomic traits suggest that most Ca. Patescibacteria require external nutrient sources through symbiotic interactions (e.g., commensal, mutualistic, and parasitic relationships) due to a lack of biosynthesis genes (Castelle et al, 2018;Fujii et al, 2022). Although previous studies demonstrated Ca.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Patescibacteria are known for their small cell (e.g., average diameter of ~0.2 μm) (He et al, 2021) and genome (e.g., 1.1±0.2 Mbp) sizes (Tian et al, 2020;Kagemasa et al, 2022), and genomic traits suggest that most Ca. Patescibacteria require external nutrient sources through symbiotic interactions (e.g., commensal, mutualistic, and parasitic relationships) due to a lack of biosynthesis genes (Castelle et al, 2018;Fujii et al, 2022). Although previous studies demonstrated Ca.…”
mentioning
confidence: 99%
“…Patescibacteria require external nutrient sources through symbiotic interactions ( e.g. , commensal, mutualistic, and parasitic relationships) due to a lack of biosynthesis genes ( Castelle et al , 2018 ; Fujii et al , 2022 ).‍ ‍Although previous studies demonstrated Ca. Patescibacteria-Bacteria interactions through cultivation-based approaches ( He et al , 2015 ; Moreira et al , 2021 ; Yakimov et al , 2022 ), cross-domain symbiosis was only reported for Ca.…”
mentioning
confidence: 99%
“…Cyanobacteria, and, Elusimicrobiota, are also found in groundwater, as well as animal gut and soil, and the latter are associated with nitrogen metabolism (31,32). Patescibacteria were also detected as part of core microbiome in males with site speci c occupancy, which have small genome size are parasitic in nature and found in groundwater in rural regions (33), therefore their prevalence may indicate exposure to rural environments. Campilobacterota, Elusimicrobiota, and Patescibacteria have been previously reported as phyla prevalent in healthy individuals from west Bengal (34).…”
Section: Discussionmentioning
confidence: 99%
“…Among these diverse bacteria, several members of the bacterial phylum Patescibacteria (also known as the Candidate Phyla Radiation/CPR superphylum), a large and diverse bacterial group consisting of uncultivated bacteria, are universally present [1−4]. Patescibacteria are characterized by their limited metabolic potential, as inferred from metagenomic analyses [2,5,6]. Furthermore, microscopic observation using techniques such as fluorescence in situ hybridization (FISH) and transmission electron microscopy (TEM) have revealed that most Patescibacteria have small cell sizes.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have highlighted that Patescibacteria parasitize other bacterial or archaeal microorganisms, suggesting a lifestyle that may compensate for their metabolic deficiencies [7−12]. Within the Patescibacteria phylum, Saccharimonadia, Paceibacteria, and Gracilibacteria are commonly detected in the activated sludge flocs [1,2,5,13], and information on Gracilibacteria has only recently been obtained by metagenomic analyses. To better understand microbial interactions in activated sludge flocs, in situ visualization using FISH or TEM within the flocs is very important because FISH probes specific for Gracilibacteria did not exist until recently.…”
Section: Introductionmentioning
confidence: 99%